Ag K- and L3-edge XAFS study on Ag species in Ag/Ga2O3 photocatalysts. (May 2016) - Yamamoto, M; Yoshida, T; Yamamoto, N; Nomoto, T; Yamamoto, A; Yoshida, H; Yagi, S
Abstract: Ag loaded Ga2 O3 (Ag/Ga2 O3 ) shows photocatalytic activity for reduction of CO2 with water. Ag L3 -edge XANES and K-edge EXAFS spectra were measured for various Ag/Ga2 O3 samples, which suggested that structural and chemical states of Ag species varied with the loading amount of Ag and the preparation method. The Ag species were metallic Ag particles with an AgGaO2 -like interface structure in the sample with high loading amount of Ag while predominantly Ag metal clusters in the sample with low loading amount of Ag. The XANES feature just above the edge represented the interaction between the Ag species and the Ga2 O3 surface, showing that the Ag metal clusters had more electrons in the d -orbitals by interacting with the Ga2 O3 surface, which would contribute the high photocatalytic activity.